Pengaruh Penggunaan Media Presentasi Lumio By Smart Pada Mata Pelajaran Aplikasi Pengolah Angka Dalam Meningkatkan Pola Pikir Kritis Siswa di Kelas VII MTs Al-Khairiyah Pipitan - Sri Wardatul Janah; Dewi Surani; Ade Fricticarani (Journal on Education, 2023)
This research is motivated by the problem of decreasing critical thinking in students when in the learning process with number processing application subjects because the learning method used by educators is a conventional method so that students pay less attention to the teacher when explaining the material and resulting in difficulties in understanding the material that the teacher delivers. And the purpose of this study is to determine the influence of the use of lumio by smart presentation media on number processing application subjects in delivering material so that students do not feel bored or bored during learning. This study used a quantitative approach with a descriptive method with grade VII students as a sample of 30 respondents and used statistical tests, namely validation tests, reality tests, simple regression tests, normality tests, t-tests and determination coefficient tests (R2). The results of the study required that there was an influence in the use of learning media (X) in improving students' critical thinking patterns (Y), with a significant value of 0.00 < 0.05 with a count of 1.70113 > table 4.445 and also a coefficient of determination test (R2) which stated that students' critical thinking increased by 41.4% with a moderate influence category with a value of 0.40-0.599. After using lumio by smart presentation media on number processing application subjects. There was an influence in using lumio by smart presentation media in the learning process and there was an increase in students' critical mindset after using lumio by smart presentation media by 41.4%